1993
DOI: 10.1557/proc-301-175
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Location and Photoluminescence of Er in GaAs and Al0.5Ga0.5As

Abstract: Epitaxial Er-doped GaAs and Al0.5Ga0.5As films, 1.6 μm thick, grown by MBE on (100) GaAs substrates at 560°C, with Er concentrations in the range 9 × 1017 to 2 × 1020 cm−3 were studied with RBS/channeling and photoluminescence techniques. Angular scans in the <110> and <111> axial and (111) planar directions indicate that the Er atoms in GaAs are located on interstitial sites. In Al0.5Ga0.5As doped with 5 × 1019 Er cm−3, 70% of the Er atoms are on positions slightly displaced from the interstitial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Observations on Er-implanted GaAs have been recently confirmed by lattice location measurements performed on molecular beam epitaxy (MBE) grown GaAs:Er epilayers [18]. Alves et al [18] have shown that directly after the growth at 5500C the Er atoms were located at the tetrahedral interstitial positions.…”
Section: Erbium In Iii-v Compoundsmentioning
confidence: 93%
See 3 more Smart Citations
“…Observations on Er-implanted GaAs have been recently confirmed by lattice location measurements performed on molecular beam epitaxy (MBE) grown GaAs:Er epilayers [18]. Alves et al [18] have shown that directly after the growth at 5500C the Er atoms were located at the tetrahedral interstitial positions.…”
Section: Erbium In Iii-v Compoundsmentioning
confidence: 93%
“…Intense intra-atomic luminescence of Er3+ could also be observed in as-grown samples. The authors have found that in MBE grown AlGaAs:Er a significant substitutional fraction of Er atoms exists, but no Er-related luminescence could be detected in this material [18].…”
Section: Erbium In Iii-v Compoundsmentioning
confidence: 96%
See 2 more Smart Citations
“…On the experimental side, a number of RBS lattice location studies revealed the following trends. In general, samples doped with Er during metalorganic chemical vapour deposition (MOCVD) [40][41][42] or molecular beam epitaxy (MBE) [43][44][45] showed the majority of Er in near-tetrahedral interstitial locations with respect to the GaAs lattice irrespective of Er concentration. In implanted samples, Er was found to prefer substitutional sites at concentrations around 10 19 cm -3 but tetrahedral interstitial around 10 20 cm -3 [46,47].…”
Section: Lattice Location Of Rare Earth Atomsmentioning
confidence: 99%